ANALISIS PENGARUH PENAMBAHAN KODE PENEBAR PADA MODULASI GMSK TERHADAP DSCDMA DAN OFDM DITINJAU DARI BER SISTEM - Al Sasongko, Sudi Mariyanto (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
The important parameter to justify the performance of a communication system is the value of Bit Error Rate, which should be small enough, the use of limited bandwidth, and the use of limited power emission. Some popular applied modulations in wireless communication for high data rate are GMSK in GSM system, QPSK in DSCDMA system, and QAM in OFDM system. This research was to simulate the performance of Bit Error Rate of GMSK which was added with a spreading code in data input.The evaluation of Bit Error Rate is done on Direct Sequence GMSK baseband and passband, Direct Sequence CDMA passband, and OFDM 64QAM baseband through AWGN channel and Multipath channel. Procedure of evaluation is simulate model with increasing SNR every 1dB until reaches threshold of BER as 10-4 . Analysis is based on program simulation in Simulink Matlab 6.5.1. Based on simulation result , for AWGN channel with threshold BER as 10 – 4 are found : DSGMSK passband have level need 1,5dB, DSCDMA passband have level need 7,5dB, DSGMSK baseband have level need 10dB, and OFDM baseband have le-vel need 27dB. In multipath channel environment, DSGMSK passband configuration is need 1,5dB less than DSCDMA configuration that are 6dB and 7,5dB.